Improving Malaysian adolescent sexual and reproductive health: An Internet-based health promotion programme as a potential intervention - Nik Farid, Nik Daliana; Mohd Arshad, Mohd Faris; Yakub, Nur Asyikin; Zaki, Rafdzah Ahmad; Muhamad, Haslina; Abdul Aziz, Norlaili; Dahlui, Maznah (SAGE Publications, 2018)
Objective: Internet-based health promotion offers a promising approach to fostering healthy sexual behaviour among adolescents. The objective of this study was to identify the potential of an Internet-based programme to improve sexual and reproductive health (SRH) knowledge among Malaysian young people. Design: A pre-test/post-test design was used to study the potential of the Malaysian Care for Adolescent Project (MyCAP) website for online SRH education. Created by health professionals, the SRH module provides detailed and accurate information about the male and female reproductive systems, the stages of adolescent development, puberty (bodily development, menstruation and wet dreams), teenage pregnancy, sexually transmitted infections (STIs) and social situations such as avoiding premarital sex. Setting: A total of 209 young adolescents aged 12 years were recruited from a school in Lembah Pantai, Kuala Lumpur. Method: Students were randomly assigned to either an Internet-based or a conventional method group. The Internet-based intervention group consisted of 101 young people (50 boys and 51 girls), while the conventional method group consisted of 108 participants (62 boys and 46 girls). Results: Using the Internet-based method, there was an increase of 3.88 in the mean knowledge score of participants from pre- to post-intervention. The Internet-based method had a greater eta-squared score of 0.59 compared to the conventional method, which had an eta-squared score of 0.41 (p <.001). Conclusion: The results revealed that the Internet-based method significantly improved adolescents’ knowledge of SRH. Since the majority of students have access to the Internet, using online learning could provide an alternative educational method for teaching SRH.